THE ROLE OF BAITUL MAL IN PUBLIC FINANCIAL MANAGEMENT: A HISTORICAL AND CONTEMPORARY PERSPECTIVE - Nur Diana Cholida; Maulida Ghina Faizah (Assets Journal: Journal of Economic and Business, 2025)
Baitul Mal functions as a separate entity from the state but maintains a close relationship with the government in managing economic and social resources for the welfare of the community. In its early days, Baitul Mal managed funds from sources such as zakat, kharaj, jizyah, and waqf, which were utilized to support economic development, social welfare, and state stability. The institutionalization of Baitul Mal began during the caliphate of Umar ibn Khattab, who transformed the management of funds from a direct distribution system to a more organized system.